2007
DOI: 10.2514/1.27460
|View full text |Cite
|
Sign up to set email alerts
|

Mach Stem Height and Growth Rate Predictions

Abstract: A new, more accurate prediction of Mach stem height in steady flow is presented. In addition, starting with a regular reflection in the dual-solution domain, the growth rate of the Mach stem from the time it is first formed till it reaches its steady-state height is presented. Comparisons between theory, experiments, and computations are presented for the Mach stem height. The theory for the Mach stem growth rate in both two and three dimensions is compared to computational results. The Mach stem growth theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 11 publications
5
68
0
Order By: Relevance
“…Related research can still be found in the recent literature. [2][3][4][5][6] In the present work, an abnormal MR configuration of asymmetric shock waves is computationally confirmed over a double-wedge geometry ͑Fig. …”
supporting
confidence: 53%
“…Related research can still be found in the recent literature. [2][3][4][5][6] In the present work, an abnormal MR configuration of asymmetric shock waves is computationally confirmed over a double-wedge geometry ͑Fig. …”
supporting
confidence: 53%
“…In comparison to the work of Mouton & Hornung (2007), we will include more fine structures than a single unsteady MR during transition and introduce a more accurate model to describe the evolution of the triple-shock structure. Inspired by the numerical simulation of Kudryavtsev et al (2002), we will perform more refined numerical simulations to identify a multiple shock interaction structure preceding the pure unsteady MR structure.…”
Section: Introductionmentioning
confidence: 99%
“…Mouton & Hornung (2007) assumed that the flow during transition contains only a single but evolutionary MR, which The symbols i, r and s refer to incident shock wave, reflected shock wave and slipline, respectively. R c refers to the major expansion fan (from the corner R).…”
Section: Introductionmentioning
confidence: 99%
“…However, he first determined the height of the Mach stem theoretically by making some assumptions about the structure of a Mach reflection, see [22]. This prediction turned out to be remarkably accurate, as may be seen in Fig.…”
Section: Caltech Stability Experimentsmentioning
confidence: 99%